Bridging performances of lost circulation materials (LC-LUBE and mica) and their blending in 80/20 and 60/40 oil-based drilling fluids - Belayneh, Mesfin; Aadnøy, Bernt (Frontiers in Physics, 2022)
In drilling wells, lost circulation, barite sagging, shale swelling, and formation damage are critical problems for the industry. These problems can be controlled by designing appropriate drilling fluids and lost circulation materials. In this study, the performance of 80/20 and 60/40 oil-based drilling fluids (OBMs) was compared based on the lost circulation materials’ (LCMs) bridging performance, filtrate loss, barite sagging, and shale stability. The results show that in terms of LCM stability, the performance of LC-LUBE improved when blended with mica. Both drilling fluids inhibit shale swelling. The overall analysis showed that the 60/40 OBM is better and recommended.